Membangun Karakter Anak Melalui Teater - Monita Precilia; Sahrul N; Sulaiman Juned (Besaung : Jurnal Seni Desain dan Budaya, 2021)
Research title is"Building of Character Children Through Theater". This research use qualitative methode with descriptive analysis. The theater performance “Run to the Moon” and the “Children's Tale” is the result of observation and the director's anger toward the children in Kampung Purus (which is usually called Kampung Puruih). Children are busy with social media so there is a lack of interaction between people. The theater performance Run to the Moon and the Children's Tale is a reality that is packed into a stage event and directly involving the children as the performer. The theater performance Run to the Moon Children’s Tale can be use to build children's character, because the message of tale invite children to interact with others, diligent study and good behavior and polite. This study aims to explore the character building of children with theater performance Run to the Moon and Children's Tale using the method of Sociology of Art and Psychotherapy.